Cholinergic system changes of falls and freezing of gait in Parkinson's disease. Issue 4 (13th March 2019) - Bohnen, Nicolaas I.; Kanel, Prabesh; Zhou, Zhi; Koeppe, Robert A.; Frey, Kirk A.; Dauer, William T.; Albin, Roger L.; Müller, Martijn L.T.M.
Abstract : Objective: Postural instability and gait difficulties (PIGDs) represent debilitating disturbances in Parkinson's disease (PD). Past acetylcholinesterase positron emission tomography (PET) imaging studies implicate cholinergic changes as significant contributors to PIGD features. These studies were limited in quantification of striatal cholinergic synapse integrity. Vesicular acetylcholine transporter (VAChT) PET ligands are better suited for evaluation of high binding areas. We examined associations between regional VAChT expression and freezing of gait (FoG) and falls. Methods: Ninety‐four PD subjects underwent clinical assessment and VAChT ([ 18 F]FEOBV) PET. Results: Thirty‐five subjects (37.2%) reported a history of falls, and 15 (16%) had observed FoG. Univariate volume‐of‐interest analyses demonstrated significantly reduced thalamic ( p = 0.0016) VAChT expression in fallers compared to nonfallers. VAChT expression was significantly reduced in the striatum ( p = 0.0012) and limbic archicortex ( p = 0.004) in freezers compared to nonfreezers. Whole‐brain voxel‐based analyses of FEOBV PET complemented these findings and showed more granular changes associated with falling history, including the right visual thalamus (especially the right lateral geniculate nucleus [LGN]), right caudate nucleus, and bilateral prefrontal regions. Freezers had prominent VAChT expression reductions in the bilateral striatum, temporal, and mesiofrontal limbic regions. Interpretation: Our findings confirm and extend on previous PET findings of thalamic cholinergic deficits associated with falling history and now emphasize right visual thalamus complex changes, including the right LGN. FoG status is associated with reduced VAChT expression in striatal cholinergic interneurons and the limbic archicortex. These observations suggest different cholinergic systems changes underlying falls and FoG in PD. Ann Neurol 2019;85:538–549